(untitled) (The Research of Medical Science Review, 2024)
Artificial Intelligence (AI) has emerged as a transformative technology in healthcare management, offering unprecedented opportunities to enhance patient care, optimize clinical workflows, and improve health outcomes. This paper presents a comprehensive review of the current state of AI applications in healthcare management, drawing upon a synthesis of empirical studies, theoretical frameworks, and expert perspectives. Key areas of focus include clinical decision support systems, predictive analytics, telemedicine, administrative automation, and digital health technologies. The literature review explores the potential benefits of AI in improving diagnostic accuracy, treatment effectiveness, and patient engagement, while also addressing challenges related to data privacy, ethical considerations, and healthcare disparities. Furthermore, the paper examines strategies for successful implementation and adoption of AI solutions, emphasizing the importance of stakeholder engagement, interdisciplinary collaboration, and evidence-based practice. The findings underscore the transformative potential of AI in revolutionizing healthcare delivery and shaping the future of medicine, while also highlighting the need for continued research, policy development, and ethical oversight to ensure responsible and equitable deployment of AI technologies in healthcare management.